Lethal Effects of a Commercial Diatomaceous Earth Dust Product on Amblyomma americanum (Ixodida: Ixodidae) Larvae and Nymphs. Issue 5 (25th April 2020) - Showler, Allan T; Flores, Nicole; Caesar, Ryan M; Mitchel, Robert D; Perez De León, Adalberto A
Abstract: With increasing development of resistance to conventional synthetic acaricides in economically and medically important ixodid species, interest in finding alternative control tactics has intensified. Laboratory bioassays were conducted, using the lone star tick, Amblyomma americanum (L.), as a model species, to assess the efficacy of a diatomaceous earth-based product, Deadzone, in comparison with a silica gel-based product, CimeXa. CimeXa is already known to be highly lethal against A. americanum larvae and nymphs. The two dust treatments were 100% effective against larvae and nymphs within 24 h after contact occurred by immersion in dry dusts and after crawling across a surface treated with the dry dusts. Contact by crawling on a dried aqueous film of the dusts, even at a concentration of 10%, was not as effective as exposure to the dusts in dry powder form. As has been demonstrated with CimeXa, it is likely that Deadzone will be capable of providing prophylactic protection of cattle from economically important one-host ixodids, such as the southern cattle fever tick, Rhipicephalus microplus (Canestrini), which vectors the causal agents of babesiosis. Diatomaceous earth can be stored indefinitely, will remain efficacious for as long as sufficient quantities remain on the substrate, it is a natural (organic) substance, and it might be amenable for limited use in environmentally protected habitats.